CDK4/6 inhibitor protects chemerin‐induced human granulosa‐lutein cells from apoptosis by inhibiting the p53/p21 waf pathway. Issue 11 (24th July 2019) - Li, Ying; Zhang, Lili; Shan, Yanhong; Jia, Chunshu; Xu, Ying
Abstract: Dysregulation of the cell cycle is common in human tumorigenesis. Therefore, CDK4/6 inhibitors targeting the cell cycle have been developed, and their antiapoptotic effects have been highly correlated with potential clinical therapies. The aim of this study was to identify the regulatory effect of the CDK4/6 inhibitor palbociclib on chemerin‐induced apoptosis of immortalized human granulosa‐lutein (hGL) cells and to elucidate its fundamental mechanism of action. Palbociclib enhanced antioxidative enzyme generation and diminished ROS generation in hGL cells. Furthermore, we found that palbociclib suppressed chemerin‐induced apoptotic protein expression, reversing the Bcl‐2/Bax ratio and inhibiting the p53/p21 waf pathway. Eventually, palbociclib decreased the level of cleaved caspase‐3 and ‐9, hindering the apoptosis of hGL cells. In general, the antiapoptotic efficacy of palbociclib could be attributed in part to the modulation of the mitochondrial apoptotic pathway in hGL cells. Abstract : Palbociclib attenuated chemerin‐mediated granulosa cell apoptosis by inactivating the p53/p21waf pathway signaling cascade. This study indicated that Palbociclib might possess therapeutic potential for PCOS.